Organisation of volunteer activities of students in the framework of inclusive education through innovative technologies - Abildina, S.; Rymkhanova, A.; Dusembinova, R.; Tebenova, K.; Riza, S. (World Journal on Educational Technology: Current Issues, 2022)
The goal of the research was to examine how student volunteerism might be organised using cutting-edge technology within the context of inclusive education, and this aspect was covered. The study employed quantitative research methodologies in its numerous aspects, and 264 volunteer students who are enrolled in different schools throughout Kazakhstan participated in the participant group. In the fall of 2021–2022. The participant groups in the study received 4-weeks of online training. The study made use of the ‘Inclusive Education and Technology’ data gathering tool, which was created by the researchers and put together by subject-matter specialists. The individuals that made up the participant groups were given the measuring tool, and it was supplied and collected online. Frequency analysis, t-test, the Kruskal-Wallis test, and the Statistical Package for the Social Sciences programme were used to analyse the data, and the results were added to the study along with the tables. Based on the research’s findings, the participant groups have high use cases for inclusive education, and it has been indicated that new technology training areas will help them.
Keywords: Inclusive education; innovative technology; organisation; online education